Industrial maxillofacial injuries in the United Kingdom. Issue 10 (December 2015) - Chiu, Geoff A.; Bullock, M.; Edwards, A.
Abstract: The treatment of maxillofacial injuries forms a substantial part of the work in oral and maxillofacial units, but injuries sustained in work-related incidents are uncommon, mainly because of the strict enforcement of Health and Safety policies. We used data from the Health and Safety Executive in the United Kingdom to review the incidence and aetiology of maxillofacial injuries that result from industrial accidents in the UK, and highlight the case of a worker who sustained an isolated fracture of the nasoethmoidal complex when he was trapped in a cheese press. In 2010-2011, roughly 115 379 accidents or incidents at work were reported in the UK, and of the 1623 (1%) that were maxillofacial, 81% occurred in the service sector. The most common mechanism of injury was assault (37%) and the most common injury was contusion (30%). Since the introduction of the Health and Safety Act, work-related accidents in the UK have decreased considerably. However, they will continue to occur because of human error.